(untitled) (Journal of Architectural Design, 2022)
The methodological path (aesthetic and functional) in advanced contemporary interior design techniques is considered one of the main episodes in interior design, as it organized in its uses scientific visualizations within a specific rational intellectual vision to reach the design output required to be implemented. What is the methodological path (aesthetic and functional) that depends on the advanced contemporary interior design techniques? Yet, the importance of research contributes to knowing the ingredients that contribute to achieving the functional and aesthetic methodological path in advanced contemporary interior design technology. The current research aims at revealing the methodological path (aesthetic and functional) that is adopted in advanced contemporary interior design techniques. The spatiotemporal dimensions are the internal spaces of reception halls of hotels of Arab design in the Middle East. Executed for the period 1999-2016. While the third chapter included the research procedures, and finally the fourth part included drawing conclusions and conclusions.